n Taksonomiese studie van Pelargonium seksie Cortusina (Geraniaceae) - Dreyer, Leanne Laurette (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1990.